Renal metastasis of ovarian granulosa cell tumor. Issue 3 (21st March 2022) - Togashi, Kyo; Yoneyama, Tohru; Sutoh Yoneyama, Mihoko; Yamamoto, Hayato; Hatakeyama, Shingo; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Futagami, Masayuki; Ohyama, Chikara
Abstract : Introduction: We would like to present a rare case of metastatic renal tumor. Case presentation: A 60‐year‐old woman presented to our department with a left renal tumor. She underwent a total hysterectomy and right adnexal resection for a stage IA ovarian granulosa cell tumor approximately 15 years ago, followed by left adnexal resection and postoperative chemotherapy with gemcitabine and paclitaxel 6 years ago. She received six courses of gemcitabine and carboplatin to treat a stage IC clear cell adenocarcinoma of the ovary. The patient was diagnosed with the left renal tumor and underwent a laparoscopic left nephrectomy. Immunostaining was positive for α‐inhibin and SF‐1 and showed FOXL2 402C→G (C134W) mutation. Finally, the patient was diagnosed with renal metastasis of a granulosa cell tumor. Conclusion: To our knowledge, this is a very rare case of renal metastasis of a granulosa cell tumor with the FOXL2 mutation in an adult.